Techno-Economic Assessment of a 100 kWp Solar Rooftop PV System for Five Hospitals in Central Southern Thailand - Rawit Khamharnphol; Ismail Kamdar; Jompob Waewsak; Somphol Chiwamongkhonkarn; Sakrapee Khunpetcha; Chuleerat Kongruang; Yves Gagnon (International Journal of Renewable Energy Development, 2023)
This paper presents a techno-economic assessment of a 100 kWp solar rooftop photovoltaic (PV) system at five hospitals in central southern Thailand.  The system encompasses 100 kWp PV panels, 100 kW grid-tied inverters and balance of system (BOS) under the grid code of the Provincial Electricity Authority (PEA).  The latest PV technology of bifacial mono-crystalline solar panels, inverters and BOS were simulated along with the Meteonorm 7.3 database using the PVsyst simulation toolkit with different tilt angles, orientations, solar radiations and ambient temperature.  The technical aspects of solar rooftop PV power generation systems include the annual energy output and the performance ratio (PR) under IEC standard.  Further, an economic analysis of the model was examined using a cost benefit analysis (CBA) and various assumptions.  Four main financial criteria, i.e., benefit cost ratio (BCR), net present value (NPV), internal rate of return (IRR), and payback period (PBP) were evaluated under three different scenarios: (1) self-consumption scheme, (2) feed-in tariff (FiT) scheme, and (3) private power purchase agreement (PPA) scheme.  Finally, the levelized cost of energy (LCOE) was also calculated.  The results reveal that the Takua Thung hospital is characterized by the maximum average global horizontal irradiation (GHI) and the maximum annual produced energy of 199 kWh/m2 and 164.8 MWh/year, respectively.  The PR calculated for all hospital sites is above 85%. The outcomes of the financial analysis show that the optimum scenarios are PPA and FiT schemes.  The LCOE analysed in this study indicates that the Takua Thung hospital site has the lowest LCOE at 2.47 THB/kWh (0.07 USD/kWh).  This research confirms the potential for hospitals and stakeholders in central southern Thailand for investments in solar rooftop PV systems